Crime Continuity and Psychological Inertia: Testing the Cognitive Mediation and Additive Postulates with Male Adjudicated Delinquents - Walters, Glenn D. (Journal of quantitative criminology, 2016)
Objectives Crime continuity is one of the best documented and least understood aspects of criminal behavior. Psychological inertia, the notion that cognitive variables mediate the relationship between earlier and later expressions of the same behavior, was tested as a possible explanation for crime continuity. Methods The cognitive mediation and additive postulates of the psychological inertia theorem were tested in a path analysis using self-report data from 1170 male delinquent members of the Pathways to Desistance study (Mulvey in Paper presented at the American Society of Criminology Annual Meeting, Chicago, IL, 2012 ). Wave 1 delinquency served as the independent variable, Wave 3 delinquency served as the dependent variable, Wave 2 outcome expectancies for crime, self-efficacy, general criminal thinking, and social capital served as the mediator variables, and 12 different baseline measures from criminological theory served as control variables in this study. Results General criminal thinking and low self-efficacy successfully mediated the relationship between past and future offending after age, race, early behavioral problems, peer criminality, family criminality, parental knowledge and monitoring, parental hostility, routine activities, measured intelligence, and precursors for each of the mediators were controlled. Social capital (cumulative disadvantage), by comparison, failed to mediate crime continuity in this study. Conclusions Effective cognitive mediation of the relationship between Wave 1 offending and Wave 3 offending and evidence that the effect may be additive offer preliminary support for the cognitive mediation and additive postulates of the psychological inertia theorem. Practical implications of these results include the need to routinely assess cognitive factors in criminal populations and target these factors for intervention.